Evaluasi penggunaan e-filling pada wajib pajak di KPP Pratama Pasar Minggu 2015-2018 - Wening Estiningsih; Hardian Mursito; Heri Nurranto (Universitas Indraprasta PGRI, 2021)
The change in service includes services to wp, from initially having to submit the taxpayer to the Tax Service Office (KPP) directly, making submitting SPT online anywhere and anytime. In addition, the use of e-filling can reduce the burden on the administration process of tax reports using paper, e-filling plays a very important role in minimizing the inaccuracy of SPT reporting data. The purpose of this study is to evaluate the use of e-filling on individual taxpayers at KPP Pratama Pasar Minggu. The research method used is a qualitative method. The results of this study show that the number of registered taxpayers from year to year continues to increase and the most number are employees of corporate taxpayers and non-employee taxpayers, meanwhile, SPT reporting uses e-filling from 2015 to year. 2019 has increased by around 58% 2019 from the number of taxpayers registered at the KPP, while it is inversely proportional to manual submission of tax returns, which means that taxpayers have begun to adapt to tax modernization.